Inhibitory Repetitive Transcranial Magnetic Stimulation to Treat Psychomotor Slowing: A Transdiagnostic, Mechanism-Based Randomized Double-Blind Controlled Trial. Issue 1 (22nd April 2020) - Walther, Sebastian; Alexaki, Danai; Schoretsanitis, Georgios; Weiss, Florian; Vladimirova, Irena; Stegmayer, Katharina; Strik, Werner; Schäppi, Lea
Abstract: Psychomotor slowing is frequently distressing patients with depression and schizophrenia. Increased neural activity within premotor cortices is linked to psychomotor slowing. This transdiagnostic study tested whether add-on inhibitory repetitive transcranial magnetic stimulation (rTMS) of the supplementary motor area (SMA) may alleviate psychomotor slowing. Forty-five patients with severe psychomotor slowing (26 psychosis, 19 major depression) were randomized in this transdiagnostic, double-blind, parallel-group, sham-controlled trial of 15 daily sessions of add-on rTMS over 3 weeks. Treatment arms included inhibitory 1 Hz stimulation of the SMA, facilitatory intermittent theta burst stimulation (iTBS) of the SMA, facilitatory 15 Hz stimulation of the left dorsolateral prefrontal cortex (DLPFC), and sham stimulation of the occipital cortex. The primary outcome was response (>30% reduction from baseline) according to the Salpêtrière Retardation Rating Scale (SRRS). Secondary outcomes were course of SRRS and further symptom rating scales. Last-observation carried forward method was applied to all subjects with baseline data. Response rates differed between protocols: 82% with inhibitory 1 Hz rTMS of the SMA, 0% with facilitatory iTBS of the SMA, 30% with sham, and 33% with 15 Hz DLPFC rTMS (χ  2 = 16.6, P < .001). Dropouts were similarly distributed across protocols. Response rates were similar in the completer analysis. This transdiagnostic trial of rTMS demonstrates that inhibitory SMA stimulation may ameliorate psychomotor slowing in severely ill patients. It further provides proof-of-concept that motor inhibition is linked to increased neural activity in the SMA because the inhibitory protocol performed best in reducing symptoms. Trial registration: NCT03275766 (www.clinicaltrials.gov ).